2008
DOI: 10.1111/j.1365-277x.2008.00886.x
|View full text |Cite|
|
Sign up to set email alerts
|

Diet quality of persons living with HIV/AIDS on highly active antiretroviral therapy

Abstract: Most of these adults living with HIV/AIDS had diets that required improvement, and being overweight was associated with poorer diet quality. Nutritional interventions aimed at maintaining healthy body weight and diet should be taken into account in caring for HIV-infected people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 8 publications
3
34
0
6
Order By: Relevance
“…Cross-behavior regulation studies show that individuals who exercise consistently report better compliance with healthy diet practices [64]. Adults living with HIV are also reported to have poor diet quality, including higher fat consumption and lower fiber intake compared to HIV-uninfected adults [65,66]. Greater central obesity, a key factor modulated by diet, is associated with a higher rate of NCI in HIV-infected individuals [53].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-behavior regulation studies show that individuals who exercise consistently report better compliance with healthy diet practices [64]. Adults living with HIV are also reported to have poor diet quality, including higher fat consumption and lower fiber intake compared to HIV-uninfected adults [65,66]. Greater central obesity, a key factor modulated by diet, is associated with a higher rate of NCI in HIV-infected individuals [53].…”
Section: Discussionmentioning
confidence: 99%
“…or micronutrient deficiencies. In a study of Brazilian PLHIV on HAART, being overweight was associated with poorer diet quality [60]. This double burden of malnutrition and overweight/obesity is an emerging problem for PLHIV, particularly in middle income countries.…”
Section: Food Insufficiency Measuresmentioning
confidence: 99%
“…Studies that measure dietary diversity using analysis of food groupings have shown that HIV-positive people often have poor diet composition, often with high numbers of starchy foods and low numbers of protein and micronutrient-dense food [70,71]. For example, Duran et al [71] used repeat 24-h recalls and the Healthy Eating Index in 56 HIV-positive people living in Brazil.…”
Section: Dietary Diversity Measuresmentioning
confidence: 99%
See 2 more Smart Citations